2021
DOI: 10.3389/fpsyg.2021.571673
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evidence of Dissociation Between Explicit Encoding and Fast Mapping of Novel Spoken Words

Abstract: Existing behavioral, neuropsychological and functional neuroimaging data suggest that at least two major cognitive strategies are used for new word learning: fast mapping (FM) via context-dependent inference and explicit encoding (EE) via direct instruction. However, these distinctions remain debated at both behavioral and neurophysiological levels, not least due to confounds related to diverging experimental settings. Furthermore, the neural dynamics underpinning these two putative processes remain poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Such an amplitude increase was not found either for the familiar words or for acoustically similar untrained control stimuli. Similar findings were obtained for implicit learning of novel words that appeared in ten different questions asked about graphical images featuring novel objects [68,69]; remarkably, in these studies the effects were found not only in the N400 time range, but also much earlier, at 170-200 ms in passive auditory ERP recordings, indicating enhanced lexical (or lexicosemantic) access of novel words after a short exposure in meaningful audio-visual contexts. In line with this, very early (from 150 ms) modulations of ERP responses to new words learned implicitly from short visually presented stories (in which only five instances of a novel word were incorporated) were also shown [70] to reflect the semantics of these novel words: concrete vs. abstract.…”
Section: Implicit Learning Of Novel Wordssupporting
confidence: 82%
See 1 more Smart Citation
“…Such an amplitude increase was not found either for the familiar words or for acoustically similar untrained control stimuli. Similar findings were obtained for implicit learning of novel words that appeared in ten different questions asked about graphical images featuring novel objects [68,69]; remarkably, in these studies the effects were found not only in the N400 time range, but also much earlier, at 170-200 ms in passive auditory ERP recordings, indicating enhanced lexical (or lexicosemantic) access of novel words after a short exposure in meaningful audio-visual contexts. In line with this, very early (from 150 ms) modulations of ERP responses to new words learned implicitly from short visually presented stories (in which only five instances of a novel word were incorporated) were also shown [70] to reflect the semantics of these novel words: concrete vs. abstract.…”
Section: Implicit Learning Of Novel Wordssupporting
confidence: 82%
“…Some studies have used audio-visual associative learning designs to directly compare explicit and implicit learning. Shtyrov and colleagues [68,69] reported that ERP patterns elicited in a passive listening paradigm by novel words immediately after the training session differed as early as at ~170 ms, and indicated a more diffuse activity for explicitly learnt words (suggestive of the executive system's involvement), as opposed to the core language areas (particularly in the temporal lobe) contributing to the implicit word acquisition from context. Moreover, behaviorally measured performance on novel words in a semantic task showed a correlation with the amplitude of an earlier ERP peak around 190 ms (putatively linked to automatic processing stages) for implicit learning, and only with a later peak (~280 ms) for the explicit acquisition, the latter being in line with the time interval of attention-related P3/P300 response [69].…”
Section: Explicit Learning and Consolidation Of Novel Wordsmentioning
confidence: 99%
“…Other studies showed no significant differences between the efficiency of two learning strategies (Warren et al, 2016;Himmer et al, 2017). Our own previous results (Shtyrov et al, 2021;Perikova et al, 2022) demonstrated very similar levels of performance for both strategies in a free recall task implemented immediately after a word learning session.…”
Section: литератураsupporting
confidence: 51%
“…Indeed, differences between the two strategies could be found at the neurophysiological level. For instance, a recent electroencephalography study found the acquisition of novel word forms to be equally successful in both conditions, whilst the patterns of ERPs elicited by items learned in EE and FM conditions differed in their scalp topography and temporal dynamics (Shtyrov et al, 2021).…”
Section: литератураmentioning
confidence: 99%
“…The aim of our project is determined by four points: (i) children tend to rely on semantics, not grammar, during sentence comprehension until they are nine years old [ 16 ]; (ii) at the age of three to six years, there is intensive maturation of the neural networks providing syntactic processes [ 40 ]; (iii) skill improvement leads to an intensive restructuring of the neural network and affects the ERP [ 61 ]; and (iv) passive voice comprehension in Russian children is the most intensive at the age of four to six [ 27 ]. The questions are: is it possible to find specific markers of the passive voice processing?…”
Section: Introductionmentioning
confidence: 99%